Troubleshooting employee behavior issues at Mutahid development finance institution - Akhmadov, Farid (ADA University, 2021)
Job satisfaction is an important issue in the field of service. Especially in such a competitive area as banking. Its importance is due to the fact that it affects the performance of the company and may affect the primary goals the company struggles to achieve. This particular consultancy project is aimed at finding the gaps in organizational behavior at Mutahid DFI, namely, the level of satisfaction of its employees with their job. The consultancy project was carried out by using the convenience sampling method through surveying 94 employees of Mutahid DFI at three branches. The data was gathered via a five point Liker scale questionnaire developed for this project, which consisted of nine facets (pay, promotion, supervision, peers, contingent rewards, fringe benefits, operating procedures, communication and nature of work) of job satisfaction as well as demographic variables. Descriptive statistics were employed in order to understand the satisfaction with each facet. Additionally, while cross-tabulations were employed in order to understand job satisfaction with each demographic variable. According to the results of the study, the general satisfaction of Mutahid DFI employees is ambivalent; this state is also seen for each facet. The employees were relatively satisfied with nature of work, supervision and promotions, whilst relatively less satisfied with operating conditions, pay and fringe benefits. Appropriate recommendations for improving the state of satisfaction were presented as a logical consequence of this study.
Keywords: Business; Job satisfaction.; Job satisfaction -- Banking area.; Organizational behavior.